Effect of bilateral intranasal transmucosal sphenopalatine ganglion block on intraoperative fentanyl requirement in children undergoing palatoplasty under general anaesthesia – A randomised, double-blinded, comparative study - Yellala Srinivas; Shubhi Singhal; Rupesh Yadav; Devang Bharti (Indian Journal of Anaesthesia)
Background and Aims: Palatoplasties are extremely painful surgeries commonly performed in children; hence, providing excellent analgesia for these surgeries is crucial. This study aims to evaluate the effect of bilateral intranasal transmucosal sphenopalatine ganglion (SPG) block on intraoperative fentanyl requirement in children undergoing palatoplasty under general anaesthesia (GA). Methods: Thirty American Society of Anesthesiologists physical status (PS) I and II patients, aged 6 months–12 years, scheduled to undergo palatoplasty, were randomised to two groups. After induction of anaesthesia, patients in Group T received bilateral SPG block using 0.5% bupivacaine-soaked cotton-tip applicators, while patients in Group C received standard anaesthesia care. The primary outcome was intraoperative fentanyl requirement, and secondary outcomes were intraoperative haemodynamics and post-extubation Paediatric Anaesthesia Emergence Delirium (PAED) scale scores at 5 and 10 min, respectively. Results: The mean intraoperative fentanyl consumption was 26.73 [standard deviation (SD): 10.19)] [95% confidence interval (CI): 20.38, 33.08] μg in Group T compared to 34.47 (SD: 12.73) (95% CI: 27.20, 41.74) μg in Group C (P = 0.008). Heart rate and mean arterial pressure were lower in Group T as compared to that in Group C (P < 0.05). PAED scale scores were recorded to be 7.33 (SD: 1.50) (95% CI: 6.47, 8.19) and 6.00 (SD: 1.31) (95% CI: 5.30, 6.70) for Group T, and 15.53 (SD: 0.74) (95% CI: 15.13, 15.93) and 14.07 (SD: 0.59) (95% CI: 13.75, 14.39) for Group C at 5 and 10 min, respectively (P < 0.001). Conclusion: SPG block causes a significant reduction in intraoperative fentanyl consumption, stabilises haemodynamics, and facilitates smoother recovery of children undergoing palatoplasty under GA.